2018
DOI: 10.1091/mbc.e17-06-0429
|View full text |Cite
|
Sign up to set email alerts
|

Tau can switch microtubule network organizations: from random networks to dynamic and stable bundles

Abstract: Tau is a neuronal microtubule bundler that is known to stabilize microtubules by promoting their growth and inhibiting their shrinkage. This study reveals novel mechanisms by which tau is able to switch microtubule network organizations via the differential regulation of microtubule bundling and dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 71 publications
1
37
0
Order By: Relevance
“…It was reported recently that the microtubule-binding protein Tau co-organizes microtubule and actin networks. 42,43 Dynamin 1 also could regulate both actin and microtubule dynamics to ensure proper podocyte function. Dynamin 1 and dynamin 2 might act coordinately to maintain the podocyte cytoskeletal structures, which is essential for their filtration function.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported recently that the microtubule-binding protein Tau co-organizes microtubule and actin networks. 42,43 Dynamin 1 also could regulate both actin and microtubule dynamics to ensure proper podocyte function. Dynamin 1 and dynamin 2 might act coordinately to maintain the podocyte cytoskeletal structures, which is essential for their filtration function.…”
Section: Discussionmentioning
confidence: 99%
“…Tau binds tubulin via its microtubule-binding domains [141], with a single tau molecule crosslinking multiple tubulin dimers [6]. Original studies found that tau stabilises microtubules [62], reducing the frequency of catastrophes (sudden microtubule disintegration) [208]. Early studies found that tau reduces the concentration of tubulin required for polymerisation [276].…”
Section: Regulation Of Microtubules: the Primary Physiological Role Omentioning
confidence: 99%
“…The functional and structural analogies between Tau and CC1 are further reflected in the fact that both Tau and CC1 are relevant for the organism to function during stress conditions; CC1 promotes cellulose synthesis during salt stress 5 , whereas Tau has emerged as a key regulator of stress-induced brain pathology in mice and oxidative stress in cultured fibroblasts 31,32 . Furthermore, similar to the tyrosine to alanine mutations in CC1, disease-related mutations in Tau cause distinct defects in microtubule organization 33 . While the typical PGGG-containing repeats of the Tau microtubule-binding domain (R1-R4) are not obvious from the CC1 sequence, the two proteins do contain four similarly spaced hydrophobic microtubule-binding regions (regions 1–4 in Fig.…”
Section: Discussionmentioning
confidence: 92%